2009
DOI: 10.1038/nrn2665
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane permeabilization in neuronal injury

Abstract: Acute neurological conditions such as cerebrovascular diseases and trauma are associated with irreversible loss of neurons and glial cells. Severe or prolonged injury results in uncontrollable cell death within the core of lesions. Conversely, cells that are less severely damaged succumb in a relatively slow fashion, frequently via the intrinsic pathway of cell death, through the deterioration of mitochondrial functions. The permeabilization of mitochondrial membranes determines whether cells will succumb to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
272
0
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 368 publications
(294 citation statements)
references
References 180 publications
5
272
0
17
Order By: Relevance
“…In support of this hypothesis, we find that NMNAT3 overexpression following neonatal H‐I decreased the activity of calpain and caspase‐3 (Fig. 4), two proteases that are well known to be triggered by the cellular events that lead to the permeabilization and altered function of mitochondria in ischemic neurons 48, 49. Furthermore, we also observed that NMNAT3 upregulation was associated with a significant decrease in the degradation of calpastatin (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…In support of this hypothesis, we find that NMNAT3 overexpression following neonatal H‐I decreased the activity of calpain and caspase‐3 (Fig. 4), two proteases that are well known to be triggered by the cellular events that lead to the permeabilization and altered function of mitochondria in ischemic neurons 48, 49. Furthermore, we also observed that NMNAT3 upregulation was associated with a significant decrease in the degradation of calpastatin (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Reduction of GSK3 correlated strongly with caspase-3 activation, this observation is consistent with the previous study by Petit-Paitel et al 38 , which demonstrated that the phosphorylation of tyr216 was involved in mitochondria dependent neuronal cell death and that inactivation of GSK3 has been proposed to be important for the neuroprotection afforded by IGF-1 and hexarelin 27,39 . 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 During acute neuronal injury, cytochrome c causes the activation and release of apoptotic protease-activating factor-1 (Apaf-1) into apoptosome, which activates caspase-9 and subsequently caspase-3 40,41 . An up-regulation of Bcl-2 suppresses this pathway 42 and therefore protects the neurons against apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…9 Owing to its central role in cell death regulation, MOMP is involved in the pathophysiology of human diseases as diverse as cancer, ischemia and viral infections. 10,11 MOMP can either be initiated at the outer mitochondrial membrane, owing to the pore-forming activity of the proapoptotic BCL-2 family members BAX and BAK, 12 or ensue the so-called "mitochondrial permeability transition" (MPT), an abrupt increase in the permeability of the inner mitochondrial Here, we reveal the important finding that the c subunit of the F O ATP synthase is required for MPT-driven mitochondrial fragmentation and cell death triggered by cytosolic calcium overload and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%